Simulation of 3-phase matrix converter using space vector modulation - K. Selvakumar; R. Palanisamy; Arul Rayappan Stalin; P. Gopi; P. Ponselvin; K. Saravanan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper illustrates the simulation of 3-phase matrix converter using Space Vector Modulation (SVM). Variable AC output voltage engendered using matrix converter with bidirectional power switches controlled by appropriate switching pulse. The conventional PWM converter engenders switching common mode voltage across the load system terminals, which cause to common mode current and its leads to bearing failure in load drive. These problems can be rectified using SVM and which minimize the effect on the harmonic fluctuation in AC output voltage and stress on the power switch is reduced using bidirectional switch for proposed 3-phase matrix converter. The simulation results have been presented to validate the proposed system using matlab / simulink.